Student Position and Learning Effectiveness in Different Teaching Methods in Higher Education - Nedim Čirić; Mustafa Veladžić (Društvene i Humanističke Studije)
This study examines the position and role of students in relation to the prevalence and effectiveness of different forms of instructional work in higher education. The aim of the study was to investigate the distribution of various instructional methods, the level of student participation and engagement in relation to the predominant teaching approaches, and how students evaluate the effectiveness of learning depending on the applied instructional method.The research is cross-sectional in nature and is based on a mixed methodological approach. A survey variant of the analytical-descriptive method was applied, along with comparative and theoretical analysis methods. A non-standardized instrument, specifically designed and adapted for the purposes of this research, was used.The research sample consists of 400 respondents of different genders, ages, academic achievements, and years of study from the University of Tuzla and the University of Bihać. The initial research hypothesis assumed that the frontal teaching method is dominant, that students perceive their role in the teaching process as predominantly passive and observational, and that there are differences in the perception of the prevalence and effectiveness of learning depending on the sociodemographic characteristics of the respondents.The research findings indicate that group work is the most prevalent form of instructional organization in higher education and is also perceived by respondents as the most effective method of learning. Conversely, the frontal teaching method is rated as the least effective, even though respondents perceive it as the least represented in the organization of instruction.